2021
DOI: 10.3390/molecules26216681
|View full text |Cite
|
Sign up to set email alerts
|

Labdane Diterpenoids from Salvia tingitana Etl. Synergize with Clindamycin against Methicillin-Resistant Staphylococcus aureus

Abstract: Quorum-sensing (QS) is a regulatory mechanism in bacterial communication, important for pathogenesis control. The search for small molecules active as quorum-sensing inhibitors (QSI) that can synergize with antibiotics is considered a good strategy to counteract the problem of antibiotic resistance. Here the antimicrobial labdane diterpenoids sclareol (1) and manool (2) extracted from Salvia tingitana were considered as potential QSI against methicillin-resistant Staphylococcus aureus. Only sclareol showed syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 138 publications
1
10
0
Order By: Relevance
“…The results showed that 65 has a synergistic effect with CD (FICI was 0.45); the study also found that 65 can bind to the AgrA protein, which may disable AgrA signal receptors. Once the AgrA signal receptor is disabled, it inhibits the release of virulence factors of S. aureus, which also shows that 65 binding to CD can effectively inhibit the QS system in bacteria and treat bacterial infection [74].…”
Section: Combination Of Other Antibiotics and Qsismentioning
confidence: 93%
See 1 more Smart Citation
“…The results showed that 65 has a synergistic effect with CD (FICI was 0.45); the study also found that 65 can bind to the AgrA protein, which may disable AgrA signal receptors. Once the AgrA signal receptor is disabled, it inhibits the release of virulence factors of S. aureus, which also shows that 65 binding to CD can effectively inhibit the QS system in bacteria and treat bacterial infection [74].…”
Section: Combination Of Other Antibiotics and Qsismentioning
confidence: 93%
“…Unlike the mainstream antibiotics described above, relatively few studies have been conducted on the combination of fusidic acid (FA) or clindamycin (CD) with QSIs. However, this drug combination provides a new direction for the fight against S. aureus or its resistant strains [72][73][74].…”
Section: Combination Of Other Antibiotics and Qsismentioning
confidence: 99%
“…Importantly, the wide-spectrum effect against filoviruses of SCL has been proposed, especially, SCL was considered as Ebola virus (EBOV) entry inhibitor by interfering the viral fusion process (EC 50 = 2.4 μm) ( Chen Q. et al, 2020 ). In antibiotic resistance, SCL performed synergistic effect with clindamycin against Methicillin-resistant Staphylococcus aureus ( Iobbi et al, 2021 ) . SCL also exerted antifungal synergies with Curcumin towards various fungus, including Candida albicans , C. glabrata , Aspergillus fumigatus ( Augostine and Avery, 2022 ).…”
Section: Pharmacological Activities Of Sclareolmentioning
confidence: 99%
“…The labdane diterpenoids sclareol and manool from Salvia tingitana are considered potential QSIs against methicillin-resistant S. aureus (MRSA). They can inhibit MRSA biofilm formation and virulence factor expression by prevention of the activation of AgrA upon binding or phosphorylation of the helper gene regulator AgrA to DNA ( Iobbi et al, 2021 ). Guo et al investigated the effect of andrographolide, the main active ingredient of Andrographis paniculata , on the pathogenies of APEC O78.…”
Section: Quorum Sensingmentioning
confidence: 99%